Role of Physical Therapy in Improving Function in Elderly Population: Enhancing Function and Independence through Physiotherapy (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Elderly people returning from injury or illness who are suffering from chronic pain, physiotherapy can help to relieve pain and restore physical functions such as flexibility, strength, balance and coordination.Elderly physiotherapy merge a combination of approaches including stretching, walking, massage, hydrotherapy, and electrical stimulation among others.The goal of physiotherapy for elderly is to make daily tasks and activities easier and to make elderly people independent as possible.